588Plasma concentrations of persistent organic pollutants and pancreatic cancer risk. (2nd September 2021) - Porta, Miquel; Gasull, Magda; Pumarega, José; Kiviranta, Hannu; Rantakokko, Panu; Raaschou-Nielsen, Ole; Bergdahl, Ingvar; Sandanger, Torkjel Manning; Rylander, Charlotta; Nøst, Therese Haugdahl; Duell, Eric; Katzke, Verena; et al.
Abstract: Background: Findings and limitations of previous studies on persistent organic pollutants (POPs) and pancreatic cancer risk support conducting further research in prospective cohorts. Objective: To investigate the association between plasma concentrations of selected POPs and pancreatic cancer risk. Methods: Prospective case-control study nested within the EPIC cohort. Participants were 513 pancreatic cancer cases and 1020 matched controls. Concentrations of 22 POPs (organochlorine pesticides, polychlorinated biphenyls, and polybrominated diphenyl ethers) were measured in plasma collected at baseline by GC-MS/MS. Results: Some, generally moderate effects were observed at higher concentrations of p, p' -DDT, trans-nonachlor, β-hexachlorocyclohexane, and the sum of 6 organochlorine pesticides and of 16 POPs. The odds ratio (OR) for the upper quartile of trans-nonachlor was 1.55 (95% confidence interval 1.06 to 2.26; P for trend=0.025). Associations were stronger in the groups predefined as most valid or relevant. Among participants having fasted >6 hours at blood collection, the ORs were significant for 10 of 11 exposure categories. Higher ORs were also observed among cases with microscopic confirmation than in cases with a clinical diagnosis. Higher ORs were also observed among normal-weight participants, with relevant estimates for all 11 exposure categories. Among participants with a follow-up ≥10 years, estimates were also higher (e.g., for trans-nonachlor: OR = 2.14, 1.01 to 4.53, P for trend=0.035). Overall, trans-nonachlor, 3 PCBs, and the 2 sums of POPs were the exposures more clearly associated with pancreatic cancer risk. Conclusions: A few moderately increased risks were apparent for the highest concentrations of certain POPs, sometimes with a dose-response relationship.